Exhibitions, Music and the British Empire - Kirby, Sarah (Musicologist) (Music in Britain, 1600-2000., 2022)
Combining approaches from reception studies and historical musicology, this book demonstrates how the representation of music at exhibitions drew the press and public into debates about music's role in society.